Highly angle-sensitive and efficient optical metasurfaces with broken mirror symmetry - Kim Nayoung; Kim Myungjoon; Jung Joonkyo; Chang Taeyong; Jeon Suwan; Shin Jonghwa (Nanophotonics)
Optical metasurfaces have great potential to overcome the functional limitations of conventional optical devices. In addition to polarization- or wavelength-multiplexed metasurfaces, angle-multiplexed metasurfaces can provide new degrees of freedom, enabling previously unrealized complex functionality in diverse applications such as LiDAR, augmented reality glasses, and imaging. However, there have been fundamental trade-offs in transmission efficiency and angular sensitivity for practically important paraxial rays. In this paper, we overcome this limitation by breaking mirror symmetries of single-layer metasurface structures. Based on an effective medium theory, we intuitively explain which material parameters affect the sensitivity and efficiency and prove that high sensitivity and high efficiency can be achieved simultaneously by breaking the mirror symmetry. Based on this, we propose optimized metasurfaces for two applications: an angle-multiplexed beam-steering device with up to 93% relative efficiency and an angle-multiplexed metalens array that can break the fundamental resolution–density trade-off of microlens arrays with high efficiency. The proposed angle-selective designs could pave the way for the development of new classes of compact optical devices with novel functions.